Distinguishing Common Ratio Preferences from Common Ratio Effects Using Paired Valuation Tasks - McGranaghan, Christina; Nielsen, Kirby; O’Donoghue, Ted; Somerville, Jason; Sprenger, Charles D. (American Economic Review, 2024)
Without strong assumptions about how noise manifests in choices, we can infer little from existing empirical observations of the common ratio effect (CRE) about whether there exists an underlying common ratio preference (CRP). We propose to solve this inferential challenge using paired valuations, which yield valid inference under common assumptions. Using this approach in an online experiment with 900 participants, we find no evidence of a systematic CRP. To reconcile our findings with existing evidence, we present the same participants with paired choice tasks and demonstrate how noise can generate a CRE even for individuals without an associated CRP. (JEL C91, D81, D91)